Students' Perceptions of Mathematics Teachers: Personal and Interpersonal - Firly; Toheri Toheri; Arif Muchyidin (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
Based on student perceptions, this study describes mathematics teachers' personalities and social competence at MTsN 2 Cirebon. This study examines and describes mathematics teachers' personalities and social competencies based on student perceptions of MTsN 2 Cirebon. This type of research uses mixed research methods and a sequential explanatory design. The population in this study was all class VIII MTsN 2 Cirebon, and the sample in this study was 134 students. The data collection techniques are questionnaires and interviews using instruments like questionnaire results and interview guidelines. The data analysis used is descriptive statistics and descriptive qualitative. The results showed that the description of the personality competence of mathematics teachers at MTsN 2 Cirebon, according to the analysis of student perceptions in general, was categorized as good with a percentage of 72.67%, which was supported by the results of student interviews stating that the teacher always dressed neatly and according to the official schedule, starting and ending timely learning. However, there are indicators of personality competence that have not been maximized, namely the teacher being a role model for students, with a smaller percentage than the other three indicators of personality competence, namely 68.38%. Moreover, the social competence of mathematics teachers at MTsN 2 Cirebon, according to the analysis of student perceptions in general, is categorized as good. Supported the results of student interviews state that the teacher, when in class, interacts well with students and cares about students by reprimanding, advising, and repeating learning that has not been understood, but if outside the classroom, the teacher is just ordinary, not so close, just saying hello like other teachers.